Additional over-the-scope-clip closure can shorten endoscopic vacuum therapy for postoperative upper gastrointestinal leakage - Kollmann, Lars; Weich, Alexander; Gruber, Maximilian; Flemming, Sven; Meining, Alexander; Germer, Christoph-Thomas; Lock, Johann Friso; Seyfried, Florian; Brand, Markus; Reimer, Stanislaus (Endoscopy International Open, 2024)
Background and study aims Endoscopic vacuum therapy (EVT) has become the most effective therapeutic option for upper gastrointestinal leakage. Despite its efficiency, this treatment can necessitate a long hospitalization. The aim of this study was to evaluate whether additional use of an over-the-scope-clips (OTSC) closure after successful EVT can shorten leakage therapy.Patients and methods All patients treated with EVT for leakages in the upper gastrointestinal tract at our center from 2012 to 2022 were divided into two propensity matched cohorts (EVT+OTSC vs. EVT only). The EVT+OTSC patients received OSTC application at the end of successful EVT directly after removal of the last sponge. The primary endpoint was the time interval from leakage diagnosis until discharge. Secondary endpoints included EVT efficacy, complications, and nutritional status at discharge.Results A total of 84 matched patients were analyzed. EVT efficacy was 100% in both groups. The time interval from leakage until discharge was significantly shorter in the EVT+OTSC vs. EVT group (33 [19–48] vs. 46 days [29–77] P = 0.004). No patient in the EVT+OTSC group required additional procedures for leakage management, whereas five (12%) in the EVT group needed additional stent placement (P = 0.021). More patients could be discharged on sufficient oral nutrition in the EVT+OTSC group (98% vs. 60%; P < 0.001).Conclusions The addition of OTSCs after successful EVT is safe and has the potential to shorten leakage therapy, enabling earlier discharge along with better functional outcomes.
Keywords: Quality and logistical aspects; Quality management; Performance and complications; GI surgery